2011
DOI: 10.1021/bc1004813
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of PEGylated Toll Like Receptor 7 Ligands

Abstract: Toll like receptor 7 (TLR7) is located in the endosomal compartment of immune cells. Signaling through TLR7, mediated by the adaptor protein MyD88, stimulates the innate immune system and shapes adaptive immune responses. Previously, we characterized TLR7 ligands conjugated to protein, lipid or polyethylene glycol (PEG). Among the TLR7 ligand conjugates, the addition of PEG chains reduced the agonistic potency. PEGs are safe in humans and widely used for improvement of pharmacokinetics in existing biologics an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
64
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(67 citation statements)
references
References 28 publications
3
64
0
Order By: Relevance
“…6,11,14 Improvement of immunostimulatory potencies of small molecule TLR7 ligands have been achieved by conjugation and formulation. 17,18,41,42 In previous studies, we demonstrated that conjugation of macromolecules, such as albumin, phospholipids and polyethylene glycol, to small molecule TLR7 ligands enhanced the immunostimulatory activities and efficacy as vaccine adjuvants. 17,18 Kedl, et al also reported that the conjugation of TLR7 ligand to proteins is necessary for enhancement of immunostimulatory activity.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…6,11,14 Improvement of immunostimulatory potencies of small molecule TLR7 ligands have been achieved by conjugation and formulation. 17,18,41,42 In previous studies, we demonstrated that conjugation of macromolecules, such as albumin, phospholipids and polyethylene glycol, to small molecule TLR7 ligands enhanced the immunostimulatory activities and efficacy as vaccine adjuvants. 17,18 Kedl, et al also reported that the conjugation of TLR7 ligand to proteins is necessary for enhancement of immunostimulatory activity.…”
Section: Discussionmentioning
confidence: 98%
“…17,18,41,42 In previous studies, we demonstrated that conjugation of macromolecules, such as albumin, phospholipids and polyethylene glycol, to small molecule TLR7 ligands enhanced the immunostimulatory activities and efficacy as vaccine adjuvants. 17,18 Kedl, et al also reported that the conjugation of TLR7 ligand to proteins is necessary for enhancement of immunostimulatory activity. 41 Polysaccharides have been used to increase immunostimulatory potency of TLR9 ligands.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations